Maternal Anemia as a Contributing Risk for Preterm Birth and Low birth weight - Munmun, Salma Akter; Ara, Rowson; Islam, Sabiha; Rahman, Reefaat; Noor, Farah; Ara, Anjumun; Wahid, Fatima; Shahinoor, A.M. (Journal of Neonatal Surgery, 2025)
Background: Maternal anemia is a common pregnancy complication, particularly in low- and middle-income countries, and is strongly associated with adverse perinatal outcomes. Aim of the study: This study aimed to assess the association between maternal anemia and the risk of preterm birth and low birth weight among pregnant women in Bangladesh. Methods: A retrospective observational study was conducted among 140 pregnant women admitted for delivery. Participants were categorized into anemic (n=70) and non-anemic (n=70) groups based on WHO hemoglobin cut-offs. Maternal sociodemographic, obstetric, and neonatal data were analyzed using descriptive statistics, chi-square tests, and logistic regression. Result: Preterm birth (<37 weeks) was significantly more frequent in anemic mothers than in non-anemic mothers (27.14% vs. 12.86%, p<0.01), as was low birth weight (<2500 g) (34.29% vs. 10.0%, p<0.01). Severe anemia showed the highest proportion of adverse outcomes. Low socioeconomic status and inadequate antenatal care visits (<4) were independent predictors of preterm birth, while low maternal BMI (<18.5 kg/m²) and inadequate antenatal care predicted low birth weight. Conclusion: Maternal anemia, particularly when severe, significantly increases the risk of preterm birth and low birth weight. Early detection, nutritional support, and improved antenatal care coverage may reduce these adverse outcomes